Habitando sentidos no encontro com jovens "capturados" pelo Sistema de Justiça : um estudo sobre as trajetórias de vida de adolescentes em conflito com a lei atendidos pelo Programa LAC/PSC de Vitória (ES) - Siqueira, Luziane de Assis Ruela (2011)
This work deals with the subjectivities produced by historical processes in a contemporary view driven by neoliberal capitalist logic, based on the consumption and on globalization of the economy. Thus, we believe that what we are is not a portrait of our private and individual history but it is produced from the socio-historical moment in which we are inserted. Our goal is to analyze the processes of subjectification that integrates adolescents in conflict with the law (ACL) that have passed through the Assisted Freedom Program/Service to the Community (LAC/PSC) in Vitória/ES, considering the production of meanings constructed by the young people themselves. We would like to stress that the choice of the young people that have been in the program is ethical political. Firstly because as they take part in the program and are affected by it, it is imposed the need to reflect on professional practices geared to young people that pass through the policejudicial apparatus. Secondly – yet seeing as main crossing of subjectivity "adolescents in conflict with the law" – because we believe that is the passage through the justice system – which forwards the young to such programs — which defines an ACL. To assist our analyses, we use the concept of constraint, adopted by the Psychology of Development, insofar as we look on practices developed in programs that seem to be outlining ways of life through its constituency. We believe in actions of a psychologist as strategist of life, which aims to build, with the young powerful actions, the possibility of living senses. This implies the bet in a life project that makes sense for them, not denying their suffering and difficulties. We emphasize that this is not to put adolescents fulfilling educational measures as victims (of the system or society) or to make them the villains fighting against the deterministic vision that are they are doomed to failure or crime. Understanding that a research is always an intervention, the production of a world, our goal is to produce senses in meeting with the young people who passed through the program LAC/PSC, using the technique of testimonies of life history, based on the methodology of Oral history. We have proposed the interview as something that makes it possible to break with the usual, since it can lead the interviewee to reflect on something that has never been thought of, summoning him to moments of re meaningfulness, to production of senses. We have used three testimonies of life history of young people who passed through LAC/PSC. We believe that the Public and/or Governmental programs built to bolster poor youth are confined to specific ways of life, such as criminal subjectivities. The courses seen lead to escapes, resistances and demand ethical and political actions, which focus on life, in the events and in depths of life.